ECO I BARAŃCZAK – DWA SPOSOBY MÓWIENIA O KULTURZE POPULARNEJ W EUROPIE ŚRODKOWEJ - TELICKI, MARCIN (Slavia Occidentalis, 2020)
The author’s academic goal is to check the effects of a parallel drawn between culture theoreticians known to the audience as writers. Both Umberto Eco (Apocalypse Postponed, Superman in Mass Culture) and Stanisław Barańczak (Incapacitated Reader) presented in their writing measured, non-elitist views of figments of collective imagination by referring to structuralism and semiotics – professional tools applied in literary criticism and cultural studies. The article offers a diagnosis of the position of the texts in question at the time of their origin. It also shows the reception of the ideas of the Polish and Italian literary critics and their creative continuations. A closer look at the specific theories related to terminology (mass culture – elitist culture), the role of the media and concealed rhetoric mechanisms leads to questions about the perspective of research into culture in the course of dynamic changes.